Enlightenment Ideals and Belief in Progress in the Run-up to the Industrial Revolution: A Textual Analysis - Ali Almelhem; Murat Iyigun; Austin Kennedy; Jared Rubin (The Quarterly Journal of Economics, 2026)
Abstract We trace the evolution of the language of science, religion, and political economy in the centuries leading to the British Industrial Revolution. Using textual analysis of 264,443 works printed in England between 1500 and 1900, we test whether British culture manifested a belief in progress associated with science and industry. Our analysis yields three main findings. First, there was a separation in the languages of science and religion beginning in the mid-eighteenth century. Second, volumes using language at the nexus of science and political economy became more progress-oriented during the Enlightenment. Third, volumes using industrial language—especially those at the science-political economy nexus—were more progress-oriented beginning in the eighteenth century.